Power played: a critical criminology of sport - Silva, Derek; Kennedy, Liam (Law and society series, 2022)
"This innovative collection argues that modern sport can be characterized by problematic power relations linked to violence, harm, deviance, and punishment. On the one hand, sport is a mainstay of community building, an expression of solidarity, and a means to mental and social health. On the other, there is the star player who commits sexual violence, the trans athlete whose achievements are dismissed as fraudulent, or the racist nationalism of the impassioned sports fan. Power Played illuminates how criminal/judicial discourses and practices reinforce social inequalities and blows the whistle on the harm, violence, and exploitation embedded in sport."--